2007
DOI: 10.1021/ma071696k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Route for Cyclic Olefin Polymerization:  Nonchelated Monodentate Benzimidazole Nickel(II) Complex Catalysts for Vinyl Polymerization of Norbornene

Abstract: We developed a series of nonchelated monodentate benzimidazole nickel complexes, bis [2-(2,6difluorophenyl) 4), upon activation with methylaluminoxane (MAO), which are found to be highly active for vinyl polymerization of norbornene (Nb). The polymerization activity displayed by 4 is as high as 1.68 × 10 9 g of PNb‚mol Ni -1 ‚h -1 at very high Nb/Ni ratio of 1 × 10 5 . Moreover a small amount of MAO is required to achieve such activity with high yield. The comparable high activity of 4.96 × 10 8 g of PNb‚mol N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
(30 reference statements)
8
20
0
1
Order By: Relevance
“…The coordination geometry around the cobalt is pseudotetrahedral similar observed to that of analogous nickel complexes [10]. The crystal structure of complex 2 consists of two solvent molecules per unit of the complex.…”
Section: Molecular Structures Of Cobalt Benzimidazole Complexes 1-3supporting
confidence: 53%
See 2 more Smart Citations
“…The coordination geometry around the cobalt is pseudotetrahedral similar observed to that of analogous nickel complexes [10]. The crystal structure of complex 2 consists of two solvent molecules per unit of the complex.…”
Section: Molecular Structures Of Cobalt Benzimidazole Complexes 1-3supporting
confidence: 53%
“…The ligands 1-(2-methoxybenzyl)-2-(2-methoxyphenyl)-1H-benzimidazole (MOBPBI) and 2-(2,6-difluorophenyl)-1H-benzimidazole (DFPBI) have been synthesized according to the reported procedure [10], whereas the ligand 2-methyl-1H-benzimidazole (MBI) is used as received from the commercial sources. The neutral benzimidazole cobalt derivatives [CoCl 2 (MOBPBI) 2 (1)], [CoCl 2 (DFPBI) 2 (2)] and [CoCl 2 (MBI) 2 (3)] were prepared by reaction of CoCl 2 with the proper benzimidazole derivative in dichloromethane and purified by re-precipitation in diethyl ether.…”
Section: Preparation Of the Ligands And Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower activity of the system Ni-35/MAO was due to its lower steric demand and electronic poor nature. Catalyst Ni-36 was used for further investigation and it was found that the optimal polymerization temperature was 25 • C. Furthermore, the activity dramatically decreased by several orders of magnitude when the solvent was changed from the polar ODCB to a ODCB/toluene mixture [145].…”
Section: Nn-chelate and Bis(n) Ligandsmentioning
confidence: 99%
“…[9] In the literature, two other types of nickel NHC complexes have been reported to be active as norbornene polymerization catalysts. Wang et al [20] reported activities up to 2.6 × 10 7 g (mol cat) −1 h −1 using a cationic nickel complex bearing two picolyl functionalized NHCs (1:Ni = 68 000, Al : Ni = 4500, 10 min at 80…”
Section: Catalytic Studiesmentioning
confidence: 99%